2013
DOI: 10.1124/mol.113.088567
|View full text |Cite
|
Sign up to set email alerts
|

Role of JunB in Adenosine A2BReceptor–Mediated Vascular Endothelial Growth Factor Production

Abstract: Interstitial adenosine stimulates neovascularization in part through A 2B adenosine receptor-dependent upregulation of vascular endothelial growth factor (VEGF). In the current study, we tested the hypothesis that A 2B receptors upregulate JunB, which can contribute to stimulation of VEGF production. Using the human microvascular endothelial cell line, human mast cell line, mouse cardiac Sca1-positive stromal cells, and mouse Lewis lung carcinoma (LLC) cells, we found that adenosine receptordependent upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
(61 reference statements)
1
22
0
Order By: Relevance
“…In agreement with previously documented adenosine actions [14,26,27,28], stimulation of adenosine receptors resulted in the induction of IL-6 , IL-8 and VEGF mRNA expressions in both asthmatics and control subjects (Fig. 4).…”
Section: Resultssupporting
confidence: 91%
“…In agreement with previously documented adenosine actions [14,26,27,28], stimulation of adenosine receptors resulted in the induction of IL-6 , IL-8 and VEGF mRNA expressions in both asthmatics and control subjects (Fig. 4).…”
Section: Resultssupporting
confidence: 91%
“…However, in the present study we have shown that the A 2B subtype is involved in the VEGF secretion not through HIF‐1α stimulation. Several works in literature reported a role for A 2B receptors in VEGF secretion in various cell types in a HIF‐1α‐independent way and recently a role of Jun B in A 2B ‐mediated VEGF secretion has been demonstrated (Feoktistov et al, ; Ryzhov et al, ). Therefore, it is likely that different pathways may be activated by the same receptor depending on the cellular system investigated or the stimulus applied.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies, using HMEC-1 demonstrated that adenosine receptor-dependent upregulation of VEGF production was associated with an increase in VEGF transcription, activator protein 1 (AP-1) activity and transcription factor JunB (JunB) accumulation (Ryzhov et al, 2014). …”
Section: Overview Of Adenosine Receptorsmentioning
confidence: 99%